Positive Solutions for Fractional Differential Equations from Real Estate Asset Securitization via New Fixed Point Theorem. (25th November 2012) - Tao, Hao; Fu, Meichen; Qian, Ru
Abstract : We study a fractional differential equation dynamics model arising from the analysis of real estate asset securitization by using the generalized fixed point theorem for weakly contractive mappings in partially ordered sets. Based on the analysis for the existence and uniqueness of the solution and scientific numerical calculation of the solution, in further study, some optimization schemes for traditional risk control process will be obtained, and then the main results of this paper can be applied to the forefront of research of real estate asset securitization.